Analisis Faktor Penyebab Anak Terlantar di Kota Medan - Rizki, Fakhri; Zahra, Siti; Tarigan, Nur Citra Naadirah Br; Ramadani, Khayrani; Alawiah, Afriana; Tambunan, Toman Sony (CV. ITTC INDONESIA, 2024)
The number of street children in Medan City continues to increase every year. According to the Medan City Social Service, in 2019 the number of street children reached 98 people, then rose to 115 people in 2020, 122 people in 2021, and in 2022 it reached 249 people. This research aims to analyze more deeply the high number of abandoned street children in Medan City. This research uses a descriptive qualitative approach, with several methods used, namely, direct observation of street children, intensive interviews, and literature studies or literature reviews to complement the required research data. Based on this research, it was concluded that first, weak family economic factors cause a child to become an abandoned child. Second, cultural factors in the form of habits to empower children to seek sustenance as a form of contribution to strengthening family finances. Third, the difficulty in continuing formal education is caused by limited funds so that a child must seek sustenance on the streets as a life choice to support the family's economy.